ANALYSIS OF THE NEXUS BETWEEN NATIONAL SECURITY AND SOCIO-ECONOMIC DEVELOPMENT - Otakey Hassan, Abbas; Sulayman, Sani; Jafaru, Yakubu; Abdullahi Enagi, Fatima; Abdullahi Enagi, Fatima (African Journal of Social and Behavioural Sciences, 2024)
This paper analysed the nexus between National Security and Socio-economic Development. In the study, we proposed a conceptual framework for examining the concept of national security and development; the paper also examined various types of national security; the paper presents perspectives of scholarly thinking about national security and its Interconnectedness with socio-economic development. The paper also identified objectives, elements/components used to measure socio-economic development. Furthermore, the paper identified some national security threats that have disruptive effects on Nigerian society due to their impact on national security and on critical infrastructure such as basic social amenities, economic and agriculture sector. The study utilized secondary sources to review literature, such as articles, journals, expert interviews, essays, and national policy documentation. Finally, we explore the proposed framework from an empirical perspective and apply it to Nigeria. Social Contract theory was adopted to explain and understand. The nexus between national security and socio-economic development.